Eksistensi Adat Istiadat Partuturan Dalam Menjaga Sistem Kekerabatan Pada Suku Batak Di Balikpapan - Lumbantoruan, Grace Mayrhoza Palimbu; Jamil, M; Hardoko, Aloysius; Pardosi, Jawatir (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Indonesia is a multicultural country where there is a lot of diversity in it ranging from the diversity of cultures, religions, languages, races, to ethnicities. There are more than a thousand tribes in Indonesia, one of which is the Batak tribe. The Batak tribe has many traditions in it, ranging from wedding customs, burials, to communication or what can be called partuturan. Partuturan is a kinship system in the Batak tribe where partuturan expresses kinship relationships between individuals in Batak culture. Until now, partuturan is still used by the Batak people both in North Sumatra and by the Batak people who migrated and are outside North Sumatra where the city is the city of Balikpapan. However, even so, the Batak community in the city of Balikpapan still applies partuturan in daily life when talking to fellow Batak tribes, so that the author is interested in researching the existence of partuturan in the Batak community in the city of Balikpapan. Therefore, this study was conducted to examine the existence of partuturan culture in the Batak community in the city of Balikpapan This research was conducted using a descriptive qualitative research method in which the author interviewed two Batak communities in the city of Balikpapan, both traditional elders and the Batak community who are considered to still understand the partuturan culture. From the results of the research that has been carried out, it can be known that the culture of speech is a way of communicating with the Batak community where speech has its own rules in its pronunciation. In the city of Balikpapan until now, partuturan still exists very much by the Batak people both with direct communication and communication through mobile phones.